Anode material for non-ferrous metal electrodeposition and preparation method thereof
By preparing the β-PbO2-MOFs coating modified by metal organic frames by composite electrodeposition method on the surface of stainless steel, the problem of high overpotential of the anode oxygen evolution reaction in copper electrolytic deposition is solved, and high efficiency and energy saving and corrosion resistance are improved.
Patent Information
- Application Number
- CN202411667895.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
AI Technical Summary
During the existing copper electrolytic deposition process, the overpotential of the anode oxygen evolution reaction is high, resulting in an increase in energy consumption. The traditional ternary alloy anode materials have problems such as easy deformation and poor corrosion resistance.
A composite electrodeposition method is used to prepare a β-PbO2-MOFs coating modified by metal organic frame on the surface of stainless steel to form a multi-layer composite anode material, refine the crystal size, improve the specific surface area and corrosion resistance.
It effectively reduces the energy consumption and resource waste of copper electroplating process, improves the oxygen evolution activity and corrosion resistance of the anode material, and extends the service life.
Smart Images

Figure CN119491275A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of non-ferrous metal electrowinning, and in particular relates to an anode material for non-ferrous metal electrowinning and a preparation method thereof. Background Art
[0002] Electrowinning is a well-known industrial method for the production of high-purity copper. Approximately 20% of copper production is carried out annually using electrowinning. However, the recovery and production of copper metal using electrowinning involves high operating costs, which is a result of high energy consumption due to high electrolysis voltage and polarization. The standard anodic reaction in copper electrowinning is the oxygen evolution reaction 2H2O=O2+4H + +4e - , E θ =1.23V, the main cathode reaction is the deposition of copper Cu 2+ +2e - =Cu,E θ =0.34 V. In industrial copper electrolytic deposition, typical operating conditions are an electrolytic voltage of about 2 V, a copper ion concentration of about 50 g / L, and a current density of 20 to 45 mA / cm 2 , the temperature is 40-60°C, the current efficiency is 89-94%, and the specific energy consumption of copper is 1.8-2.5 kWh / kg. Usually, some form of solution movement is maintained to achieve rapid and stable mass transfer, and higher copper concentrations reduce mass transfer limitations, thereby improving current efficiency. Since high current density during electrolytic deposition also increases ohmic resistance losses in solution, small operating current density is often associated with low power consumption. When no efficiency loss occurs, the theoretical minimum energy consumption of industrial copper electrolytic deposition is 0.75 kWh / kg Cu. Among them, the anodic reaction accounts for about 70% of the total energy consumption of industrial copper electrolytic deposition. Therefore, to reduce the energy consumption in copper electrowinning, reducing the overpotential of the anodic oxygen evolution reaction is of paramount importance. Among them, selecting a suitable anode material is an important means to reduce the overpotential of oxygen evolution.
[0003] Hydrometallurgy usually uses ternary alloy lead-calcium-tin (Pb-Ca-Sn) as anode material. Pb-Ca-Sn alloy has the disadvantages of high oxygen evolution potential, easy deformation, poor corrosion resistance, strong pollution, etc. Therefore, in order to obtain highly active and corrosion-resistant copper electrowinning anode materials, it is an inevitable requirement of today's society to develop a new generation of industrial electrolytic electrode materials to make efficient use of the anode product environment. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes an anode material for non-ferrous metal electrodeposition and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing an anode material for non-ferrous metal electrodeposition, comprising the following steps: subjecting stainless steel to an alkali-boiling degreasing treatment and then electro-depositing α-PbO2 on the surface of the stainless steel to obtain stainless steel / α-PbO2; and then preparing a metal organic framework-modified β-PbO2-MOFs coating on the surface of the stainless steel / α-PbO2 by a composite electrodeposition method to obtain the anode material for non-ferrous metal electrodeposition.
[0007] Preferably, the temperature of the alkali boiling degreasing treatment is 50-70° C., the time is 0.5-1.5 h, and the alkali used in the alkali boiling degreasing treatment is a NaOH solution with a concentration of 20-30 wt%.
[0008] Preferably, the formula of the plating solution for electrodeposition of α-PbO2 is: 120-140 g / L NaOH and 44.46-55.8 g / L PbO.
[0009] Preferably, the deposition conditions of the electrodeposition of α-PbO2 are: current density 30-40 mA·cm -2 , temperature 40-60℃, time 1-1.5h, stirring speed of the plating solution 200-300r / min.
[0010] Preferably, the composite electrodeposition method is used to prepare the metal organic framework modified β-PbO2-MOFs coating on the stainless steel / α-PbO2 surface. Specifically, a titanium mesh is used as a cathode, stainless steel / α-PbO2 is used as an anode, and a mixed solution containing a metal organic framework is used as an electroplating solution. A composite electrodeposition method is used to prepare the metal organic framework modified β-PbO2-MOFs coating on the stainless steel / α-PbO2 surface.
[0011] Preferably, the deposition conditions of the composite electrodeposition method are: current density 25-30 mA·cm -2 , temperature 40~60℃, time 1.5~2.5h, stirring speed of the plating solution 300~400r / min.
[0012] Preferably, the mixed solution containing the metal organic framework includes the following components: 178.1-200 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5-10 g / L Cu(NO3)2, 1-10 g / L metal organic framework and 0.05-0.06 M surfactant.
[0013] Preferably, the preparation method of the metal organic framework comprises: adding hydrated copper nitrate and nickel nitrate hexahydrate into a mixed solvent, then adding trimesic acid, and reacting at 170-200° C. for 6-8 hours to obtain the metal organic framework.
[0014] Preferably, the mixed solvent is formed by mixing anhydrous ethanol, water and N,N-dimethylformamide in a volume ratio of 1:1:1.
[0015] The present invention also provides an anode material for non-ferrous metal electrodeposition prepared by the preparation method described in the above technical solution.
[0016] Compared with the prior art, the present invention has the following advantages and technical effects:
[0017] The present invention adopts composite electrodeposition to prepare β-PbO2-MOFs multilayer composite material, and combines metal organic framework (MOFs) to modify the modified PbO2 electrode. MOFs can embed PbO2 crystals, refine the crystal size, and increase the crystal specific surface area. At the same time, the good coordination structure of MOFs effectively eliminates the internal stress between the coatings, improves the corrosion resistance and oxygen evolution activity of the electrode, effectively reduces the energy consumption and resource waste of copper electrowinning, and achieves high efficiency and energy saving.
[0018] The present invention prepares a novel multilayer composite anode material through metal organic framework modification and composite electrodeposition technology. By modifying the PbO2 electrode through the metal organic framework, the oxygen evolution overpotential of the hydrometallurgical copper anode is effectively reduced, the oxygen evolution activity and corrosion resistance of the electrode are improved, the service life of the electrode material is guaranteed, and the energy consumption and resource waste of copper electrodeposition are effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0020] Figure 1 Surface morphology of the metal organic framework (MOFs) in Example 1;
[0021] Figure 2 This is a surface morphology of the anode material for non-ferrous metal electrodeposition prepared in Example 1;
[0022] Figure 3 These are the test results of the oxygen evolution catalytic activity of the anode materials in Comparative Example 2 and Example 1. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] An embodiment of the present invention provides a method for preparing an anode material for non-ferrous metal electrodeposition, comprising the following steps: subjecting stainless steel to an alkali boiling and degreasing treatment, and then electrodepositing α-PbO2 on the surface of the stainless steel to obtain stainless steel / α-PbO2; and then preparing a metal organic framework-modified β-PbO2-MOFs coating on the surface of the stainless steel / α-PbO2 by a composite electrodeposition method to obtain the anode material for non-ferrous metal electrodeposition.
[0026] In a preferred embodiment, the temperature of the alkali degreasing treatment is 50-70°C, the time is 0.5-1.5h, and the alkali used in the alkali degreasing treatment is a NaOH solution with a concentration of 20-30wt%. The present invention removes oil stains on the surface of stainless steel through alkali degreasing treatment, thereby improving the bonding strength between the stainless steel substrate and the coating.
[0027] In a preferred embodiment, the electroplating solution formula of the electroplating α-PbO2 is: 120-140 g / L NaOH and 44.46-55.8 g / L PbO; the deposition conditions of the electroplating α-PbO2 are: current density 30-40 mA·cm -2 , temperature 40-60°C, time 1-1.5h, stirring speed of the electroplating solution 200-300r / min. The present invention deposits α-PbO2 under the above deposition conditions, which is conducive to obtaining an intermediate α-PbO2 coating with strong bonding force.
[0028] In a preferred embodiment, the composite electrodeposition method is used to prepare a metal organic framework modified β-PbO2-MOFs coating on a stainless steel / α-PbO2 surface. Specifically, the titanium mesh is used as a cathode, the stainless steel / α-PbO2 is used as an anode, and a mixed solution containing a metal organic framework is used as an electroplating solution. The composite electrodeposition method is used to prepare a metal organic framework modified β-PbO2-MOFs coating on a stainless steel / α-PbO2 surface. Metal organic frameworks (MOFs) are a type of crystalline porous material with a periodic network structure formed by self-assembly of inorganic metal centers (metal ions or metal clusters) and bridged organic ligands. It has the advantages of good stability, large specific surface area, structural rigidity, designable structure, and easy functionalization. The use of MOFs to modify PbO2 can significantly improve the catalytic activity, thereby reducing the oxygen evolution overpotential in the copper electrowinning process, and achieving the purpose of reducing energy consumption, energy saving and emission reduction.
[0029] In a preferred embodiment, the deposition conditions of the composite electrodeposition method are: current density 25-30 mA·cm -2, temperature 40-60°C, time 1.5-2.5h, stirring speed of electroplating solution 300-400r / min. The present invention can change the surface morphology, chemical composition and organizational structure of the composite material by adopting the deposition conditions of the above-mentioned composite electrodeposition method, so that the surface or local performance of the material is improved. At the same time, the small size effect, surface and interface effect of the metal organic framework itself are used to give the material surface new special properties such as mechanics, thermal and physical chemistry, and obtain a multilayer PbO2 electrode, which improves the bonding force and surface activity between the electrodes.
[0030] In a preferred embodiment, the mixed solution containing the metal organic framework includes the following components: 178.1-200 g / L (CH3SO3) 2Pb, 19.22 g / L NH2SO3H, 5-10 g / L Cu(NO3) 2, 1-10 g / L metal organic framework and 0.05-0.06 M surfactant, and further preferably 178.1-200 g / L (CH3SO3) 2Pb, 19.22 g / L NH2SO3H, 5-10 g / L Cu(NO3) 2, 1-5 g / L metal organic framework and 0.05-0.06 M surfactant. The present invention is conducive to obtaining an anode material with good catalytic activity by controlling the content of the metal organic framework (MOFs) in the electroplating solution. Too high a content of the metal organic framework (MOFs) in the electroplating solution will cause excessive adsorption of the metal organic framework on the electrode surface, resulting in surface agglomeration, which is not conducive to improving the surface activity of the electrode.
[0031] In a preferred embodiment, the surfactant comprises C 12 H 25 SO3Na.
[0032] In a preferred embodiment, the preparation method of the metal organic framework comprises: adding hydrated copper nitrate and nickel nitrate hexahydrate into a mixed solvent, then adding trimesic acid, and reacting at 170-200° C. for 6-8 hours to obtain the metal organic framework Cu-Ni MOF.
[0033] In a preferred embodiment, the mixed solvent is formed by mixing anhydrous ethanol, water and N,N-dimethylformamide in a volume ratio of 1:1:1.
[0034] In a preferred embodiment, the mass ratio of the hydrated copper nitrate, the hydrated nickel nitrate and trimesic acid is 1:(2-3):5-6.
[0035] The present invention also provides an anode material for non-ferrous metal electrodeposition prepared by the preparation method described in the above technical solution.
[0036] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0037] Example 1
[0038] A method for preparing an anode material for non-ferrous metal electrodeposition:
[0039] (1) At 70° C., a 30 wt % NaOH solution is used to perform an alkali boiling degreasing treatment on the stainless steel for 1 h to obtain the treated stainless steel;
[0040] (2) Using the treated stainless steel obtained in step (1) as the anode and the titanium mesh as the cathode, α-PbO2 is electroplated on the stainless steel surface. The plating solution formula is: 120 g / L NaOH and 44.46 g / L PbO. The deposition conditions are: temperature 40°C, stirring speed of the plating solution 200 r / min, current density 30 mA cm -2 , time 1h, stainless steel / α-PbO2 was obtained;
[0041] (3) Using the stainless steel / α-PbO2 obtained in step (2) as an anode, a titanium mesh as a cathode, and a mixed solution containing a metal organic framework as an electroplating solution, a composite electrodeposition method is used to prepare a metal organic framework modified β-PbO2-MOFs coating to obtain an anode material (stainless steel / α-PbO2 / β-PbO2-MOFs) for non-ferrous metal electrodeposition, recorded as β-PbO2-MOFs (1 g L -1 ); wherein the mixed solution containing the metal organic framework is composed of the following components: 178.1g / L (CH3SO3)2Pb, 19.22g / L NH2SO3H, 5g / L Cu(NO3)2, 1g / L metal organic framework (MOFs) and 0.05MC 12 H 25 SO3Na; The deposition conditions of the composite electrodeposition method are: current density 30mA·cm -2 , temperature 60℃, time 1.5h, stirring speed of plating solution 300r / min;
[0042] The preparation method of metal organic frameworks (MOFs) is as follows: 1 g of hydrated copper nitrate and 2 g of nickel nitrate hexahydrate are added to a mixed solvent of anhydrous ethanol, pure water and N,N-dimethylformamide in a volume ratio of 1:1:1, and then 5 g of trimesic acid is added, reacted at 170°C for 6 hours, solid-liquid separation, and then the obtained solid is washed with deionized water to neutrality to obtain a metal organic framework Cu-Ni MOF.
[0043] Figure 1 is the surface morphology of the metal organic framework (MOFs) in Example 1. Figure 1 It can be seen that the surface of the synthesized MOFs is a layered structure and has a large specific surface area.
[0044] Figure 2 This is a surface morphology of the anode material for non-ferrous metal electrowinning prepared in Example 1. Figure 2 It can be seen that the surface of the anode material is covered with a layer of MOFs with a particle size of about 20 nm. The fine particles are beneficial to increasing the specific surface area of the electrode, thereby improving the catalytic activity of the electrode.
[0045] Example 2
[0046] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2, 2 g / L metal organic framework (MOFs) and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (2 g L -1 ).
[0047] Example 3
[0048] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2, 3 g / L metal organic framework (MOFs) and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (3 g L -1 ).
[0049] Example 4
[0050] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2, 4 g / L metal organic framework (MOFs) and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (4 g L -1 ).
[0051] Example 5
[0052] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2, 6 g / L metal organic framework (MOFs) and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (6 g L -1 ).
[0053] Example 6
[0054] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2, 8 g / L metal organic framework (MOFs) and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (8 g L -1 ).
[0055] Example 7
[0056] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2, 10 g / L metal organic framework (MOFs) and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (10 g L -1 ).
[0057] Comparative Example 1
[0058] The difference from Example 1 is that in step (3), the mixed solution containing the metal organic framework is composed of the following components: 178.1 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5 g / L Cu(NO3)2 and 0.05 MC 12 H 25 SO3Na, and obtain the anode material for non-ferrous metal electrowinning, denoted as β-PbO2-MOFs (0 g L -1 ).
[0059] Comparative Example 2
[0060] Pb-Ca-Sn alloy was purchased from Kunming University of Science and Technology Hengda Co., Ltd.
[0061] Figure 3 The oxygen evolution catalytic activity test results of the anode materials in Comparative Example 1 and Example 1 are shown in Figure 1. -1 ) is comparative example 1, PbO2-MOFs (1 g L -1 ) is Example 1. Figure 3 It can be seen that the β-PbO2-MOFs electrode obtained by using MOFs to modify the PbO2 electrode in Example 1 has a current density higher than that of PbO2-MOFs (0 g L -1 ) is higher, indicating that PbO2-MOFs (1g L -1 ) electrode has a lower oxygen evolution potential and higher oxygen evolution catalytic activity at the same current density, which is beneficial to reducing the oxygen evolution overpotential in the copper electrodeposition process.
[0062] Simulated copper electrowinning experiment:
[0063] The electrolysis conditions are: current density 300A·m -2 , temperature 35°C, solution volume 0.5L, solution composed of 180g / L H2SO4 and 45g / L CuSO4, anode is the anode material prepared in Example 1-7 and Comparative Example 1-2, cathode is stainless steel. Current efficiency, energy consumption per ton of copper electrodeposition and lead content of cathode copper are shown in Table 1.
[0064] Table 1 Simulated copper electrowinning experimental results of anode materials prepared in Examples 1-7 and Comparative Examples 1-2
[0065]
[0066]
[0067] From Table 1, we can see that β-PbO2-MOFs (3 g L -1 ) has the highest current efficiency of 93.85%, followed by β-PbO2-MOFs (2 g L -1 )、β-PbO2-MOFs(1g L -1 )、β-PbO2-MOFs(0g L -1), Pb-Ca-Sn alloy, and the higher the current efficiency, the greater the utilization of electricity. The Pb-Ca-Sn alloy electrode has the highest energy consumption, which is 2002.78kW·h / t, which is significantly higher than the β-PbO2-MOFs electrode prepared in Examples 1-3. In addition, the average energy consumption of the β-PbO2-MOFs electrode prepared by the present invention is about 1800kW·h / t, indicating that the modified β-PbO2-MOFs electrode has a good energy-saving effect. In addition, the lead content in copper products prepared from different anode materials is, from high to low, 0.0056% (Pb-Ca-Sn alloy), 0.0025% (β-PbO2-MOFs (0g L -1 )), 0.0014% (β-PbO2-MOFs (2g L -1 )), 0.0012% (β-PbO2-MOFs (1g L -1 )) and 0.0011% (β-PbO2-MOFs (3g L -1 )). Obviously, using MOFs to modify PbO2 can significantly reduce the lead content in copper products, improve the quality of copper products, and is conducive to the green and low-carbon development of copper smelting.
[0068] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an anode material for non-ferrous metal electrodeposition, characterized in that: The following steps are involved: After the stainless steel is subjected to an alkali boiling and degreasing treatment, α-PbO2 is electro-deposited on the surface of the stainless steel to obtain stainless steel / α-PbO2; then a metal organic framework-modified β-PbO2-MOFs coating is prepared on the surface of the stainless steel / α-PbO2 by a composite electrodeposition method to obtain the anode material for non-ferrous metal electrowinning.
2. The preparation method according to claim 1, characterized in that: The temperature of the alkali boiling degreasing treatment is 50-70° C., the time is 0.5-1.5 h, and the alkali used in the alkali boiling degreasing treatment is a NaOH solution with a concentration of 20-30 wt%.
3. The preparation method according to claim 1, characterized in that: The formula of the electroplating solution for electroplating α-PbO2 is: 120-140 g / L NaOH and 44.46-55.8 g / L PbO.
4. The preparation method according to claim 1, characterized in that: The deposition conditions of the electrodeposition of α-PbO2 are: current density 30-40 mA·cm -2 , temperature 40-60℃, time 1-1.5h, stirring speed of the plating solution 200-300r / min.
5. The preparation method according to claim 1, characterized in that: The composite electrodeposition method is used to prepare a metal organic framework modified β-PbO2-MOFs coating on a stainless steel / α-PbO2 surface. Specifically, a titanium mesh is used as a cathode, stainless steel / α-PbO2 is used as an anode, and a mixed solution containing a metal organic framework is used as an electroplating solution. The composite electrodeposition method is used to prepare a metal organic framework modified β-PbO2-MOFs coating on a stainless steel / α-PbO2 surface.
6. The preparation method according to claim 1 or 5, characterized in that: The deposition conditions of the composite electrodeposition method are: current density 25-30 mA·cm -2 , temperature 40~60℃, time 1.5~2.5h, stirring speed of the plating solution 300~400r / min.
7. The preparation method according to claim 5, characterized in that: The mixed solution containing the metal organic framework includes the following components: 178.1-200 g / L (CH3SO3)2Pb, 19.22 g / L NH2SO3H, 5-10 g / L Cu(NO3)2, 1-10 g / L metal organic framework and 0.05-0.06 M surfactant.
8. The preparation method according to claim 1 or 5, characterized in that: The preparation method of the metal organic framework comprises: adding hydrated copper nitrate and nickel nitrate hexahydrate into a mixed solvent, then adding trimesic acid, and reacting at 170-200° C. for 6-8 hours to obtain the metal organic framework.
9. The preparation method according to claim 8, characterized in that: The mixed solvent is prepared by mixing anhydrous ethanol, water and N,N-dimethylformamide in a volume ratio of 1:1:
1.
10. Anode material for non-ferrous metal electrodeposition prepared by the preparation method according to any one of claims 1 to 9.